PENGEMBANGAN MEDIA PEMBELAJARAN UNO STATIK DALAM PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING MATERI TURUNAN KELAS XI - Juni Rahwanti; Venissa Dian Mawarsari; Abdul Aziz (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Problems in this research that is learning of derivative matter about problem solving problem still considered difficult. Lack of motivation and responsibility result in problem-solving abilities also low. This study aims to develop a valid learning media and learning with learning media developed effectively. Effective is referred to in this research is to achieve mastery, the influence and the difference of average. This research is a type of development research with ADDIE Model which is an abbreviation of Analysis, Design, Development, Implementation, Evaluation. The population in this study are all students of class XI in SMA N 1 Jatinom academic year 2016/2017. Sampling technique using purposive sampling technique. Techniques used to collect data in this study are interviews, documentation, observation, questionnaires and tests. Kevalidan media product developed based on validation consisting of validation of expert media I with achievement level of 93,75%, media expert II equal to 87,5%, material expert equal to 77,5% and media user equal to 86,67%. The average achievement rate is 86.355%, so the learning media is feasible to be used. The result of completeness test of problem solving ability reaching completeness of study individually with KKM 77 counted 31 students from 38 students and mastery classically 83,87%. Result of influence test by using linear regression test in SPSS program showed that motivation and responsibility influence problem solving equal to 98,1%. The mean difference test results indicate an average difference in problem solving skills of the experimental class and control class. The average problem solving ability of the experimental class is better that 82.90 than the control class of 70.25. So the Uno Static Learning Media in the Application of Snowball Throwing Learning Model The Class XI Derivative Material is valid and effective learning. Based on the research is expected teachers can use instructional media and innovate the learning model as a means of improving motivation, responsibility and problem solving skills of learners.Keywords: Learning Media, Uno Statik, Snowball Throwing, Problem Solving Abilities.